Thermal sensitivity of black corals (Antipatharia: Hexacorallia): Comparisons between sympatric species from a thermally fluctuating site in Madagascar and between allopatric congenerics - Mathilde Godefroid; Mathilde Vandendriessche; Gildas Georges Boleslas Todinanahary; Ignace Ransquin; Philippe Dubois (Science of The Total Environment, 2024)

Thermal stress response of Antipathella wollastoni (Gray, 1857) from the Canary Islands archipelago - Adriana Gouveia; Mathilde Godefroid; Philippe Dubois; Fernando Espino; Fernando Tuya; Ricardo Haroun; Alicia Herrera; Francisco Otero-Ferrer (Coral Reefs, 2023)
The present study aims at assessing the thermal tolerance of the black coral Antipathella wollastoni (Gray, 1857), which forms extensive forests in multiple Macaronesian islands. Fragments of A. wollastoni were exposed for 15 d to temperature conditions ranging from 19 to 26.5 °C, and multiple endpoints were investigated. No mortality was observed, and total antioxidant capacity remained unaffected by temperature increase. Respiration rates described a Gaussian relationship and tissue necrosis a linear increase with temperature. Increased temperature triggered the formation of bailout propagules, a process that may be used by the species as an escape strategy under unfavourable environmental conditions. Propagules of A. wollastoni were described for the first time. Altogether, A. wollastoni was suggested to have low vulnerability to increased temperatures, owing to its wide thermal window of performance (9.7 °C) and thermal safety margin (1.2 °C), similar to its congeneric Mediterranean Antipathella subpinnata .

Higher daily temperature range at depth is linked with higher thermotolerance in antipatharians from the canary islands - Mathilde Godefroid; Adriana Gouveia; Francisco Otero-Ferrer; Fernando Espino; Fernando Tuya; Philippe Dubois (Journal of Thermal Biology, 2023)

Thermal performance with depth: Comparison of a mesophotic scleractinian and an antipatharian species subjected to internal waves in Mo'orea, French Polynesia - Mathilde Godefroid; Philippe Dubois; Laetitia Hédouin (Marine Environmental Research, 2023)

Low vulnerability of the Mediterranean antipatharian Antipathella subpinnata (Ellis & Solander, 1786) to ocean warming - Godefroid Mathilde; Zeimes Tom; Bramanti Lorenzo; Romans Pascal; Bo Marzia; Toma Margherita; Danis Bruno; Dubois Philippe; Guillaumot Charlène (Ecological Modelling, 2023)